2016
DOI: 10.1159/000453592
|View full text |Cite
|
Sign up to set email alerts
|

Unknown Primary Melanoma: Worldwide Survey on Clinical Management

Abstract: Background: How to deal with melanoma of unknown primary (MUP) origin is a debated topic in the literature. Objective: We performed a worldwide survey to inquire what clinical and investigational workup is performed as well as the physicians' perception of this disease. Methods: A questionnaire was sent via mail to clinicians involved in melanoma care from December 2015 to April 2016 using the International Dermoscopy Society website. Results: 119 physicians from 47 different countries answered the questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…19 Although there are no specific treatment recommendations for patients with MUP, physicians tend to apply similar strategies for patients with stage-matched MKP. 20 This approach is supported by the results of a large study into the molecular characterisation of patients diagnosed with MUP, in which it was shown that the clinical behaviours and molecular patterns of BRAF/NRAS alterations were similar between patients with MUP and stage-matched MKP. 21 The percentage of Dutch patients diagnosed with stage IV MUP who were primarily treated with novel therapy increased considerably during the study period.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…19 Although there are no specific treatment recommendations for patients with MUP, physicians tend to apply similar strategies for patients with stage-matched MKP. 20 This approach is supported by the results of a large study into the molecular characterisation of patients diagnosed with MUP, in which it was shown that the clinical behaviours and molecular patterns of BRAF/NRAS alterations were similar between patients with MUP and stage-matched MKP. 21 The percentage of Dutch patients diagnosed with stage IV MUP who were primarily treated with novel therapy increased considerably during the study period.…”
Section: Discussionmentioning
confidence: 88%
“…In clinical trials, these immunotherapy and targeted therapy approaches have reported median OS durations that exceed 30 months and 20 months, respectively . Although there are no specific treatment recommendations for patients with MUP, physicians tend to apply similar strategies for patients with stage‐matched MKP . This approach is supported by the results of a large study into the molecular characterisation of patients diagnosed with MUP, in which it was shown that the clinical behaviours and molecular patterns of BRAF/NRAS alterations were similar between patients with MUP and stage‐matched MKP …”
Section: Discussionmentioning
confidence: 99%
“…The brain lesion was excised and the histological examination confirmed that the melanoma showed the BRAF V600E mutation. We did not detect skin lesions that could be referred to a primary melanoma . No histological data were available from a pigmented lesion on the left big toe, removed when he was 36 years old.…”
Section: Literature Review Of Studies On the Treatment Of Cardiac Metmentioning
confidence: 99%
“…We did not detect skin lesions that could be referred to a primary melanoma. 7 No histological data were available from a pigmented lesion on the left big toe, removed when he was 36 years old.…”
mentioning
confidence: 99%
“…1,2 Once melanoma has spread into the lymph nodes, or even visceral organs and the brain, it remains a life-threatening disease despite the advent of molecular targeted or immunotherapies. 1,2 Melanoma of unknown primary (MUP) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] represents an unusual subtype of melanoma which was reported to be about 2-9% of melanoma of known primary (MKP) at all stages. 3 Some of the literature in the different geographic regions demonstrated better overall survival of MUP than of MKP.…”
Section: Introductionmentioning
confidence: 99%